The contributions of relationships with parents and teachers to Turkish children's antisocial behaviour - Acar, İbrahim Hakkı; Evans, Moon Y. Q.; Rudasill, Kathleen Moritz; Yıldız, Süleyman (Routledge Journals, Taylor & Francis Ltd, 2018)
The present study examined the concurrent contributions of parent-child and teacher-child relationship quality to Turkish children's antisocial behaviour, with a specific focus on the moderating role of teacher-child relationships (closeness and conflict) on parent-child relationships when predicting antisocial behaviour. Participants were 94 children (56 boys) with mean age of 7.05years (SD=.88) enrolled in 24 classrooms from five elementary schools in a suburban school district in Turkey. Mothers reported on their relationship with children and teachers reported on their relationships with children as well as children's antisocial behaviour. SAS PROC MIXED was used to test hierarchical regression models of children nested within classrooms. Results showed that teacher-child conflict moderated the association between parent-child conflict and children's antisocial behaviour. Such that, higher parent-child conflict was related to higher levels of antisocial behaviour at the context of higher levels of teacher-child conflict. In addition, teacher-child closeness also moderated the association between parent-child conflict and children's antisocial behaviour. Such that when teacher-child closeness was at average or high levels, lower levels of parent-child conflict was related to lower levels of antisocial behaviour. Teacher-child conflict was positively associated with children's antisocial behaviour. Limitations and future directions of the current study are discussed.
WOS: 000443987100003
Keywords: Turkish children; Antisocial Behaviour; Parent Child Relationship; Teacher Child Relationship